The roles of nausea and vomiting in COVID-19: did we miss something? - Zhang, Tongyue (J Microbiol Immunol Infect, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an international public health emergency. Although respiratory symptoms predominate the clinical manifestations of COVID-19, gastrointestinal symptoms have been observed in a subset of patients. Notably, some patients have nausea/vomiting as the first clinical manifestation of COVID-19, which is often overlooked by people. It is now clear that not only the lungs, the gastrointestinal tract could also be attacked by SARS-CoV-2. Its host receptor angiotensin-converting enzyme 2 (ACE2), which acts as a gateway to infection, has been found to be highly expressed in the gastrointestinal epithelium and may lead to the development of nausea/vomiting. Raise awareness of these symptoms and take timely intervention would help people combat the pandemic. This review discussed epidemiology, mechanisms, management, and prevention of COVID-19 related nausea and vomiting.